In Vitro Development of Bison Embryos Using Interspecies Somatic Cell Nuclear Transfer. Issue 6 (21st May 2013) - Seaby, RP; Alexander, B; King, WA; Mastromonaco, GF
Contents: Interspecies somatic cell nuclear transfer (interspecies SCNT) has been explored in many domestic and non‐domestic animal species. However, problems arise during the development of these embryos, which may be related to species‐specific differences in nuclear–cytoplasmic communication. The objectives of this study were to investigate the possibility of producing bison embryos in vitro using interspecies SCNT and assess the developmental potential of these embryos. Treatment groups consisted of cattle in vitro fertilization (IVF) and cattle SCNT as controls and wood bison SCNT, plains bison SCNT and wisent SCNT as experimental groups. Cleavage and blastocyst rates were assessed, and blastocyst quality was determined using total cell number, apoptotic incidence and relative quantification of mitochondria‐related genes NRF1, MT‐CYB and TFAM . These results indicate that embryos can be produced by interspecies SCNT in all bison species/subspecies (13.34–33.54% blastocyst rates). Although increased incidence of apoptosis was observed in bison SCNT blastocysts compared to cattle SCNT controls (10.45–12.69 vs 8.76, respectively) that corresponded with significantly lower cell numbers (80–87 cells vs >100 cells, respectively), no major differences were observed in the expression of NRF1, MT‐CYB and TFAM . This study is the first to report the production of bison embryos by interspecies SCNT. Blastocyst development in all three bison species/subspecies was greater than the rates obtained in previous studies by IVF, which supports the potential role of SCNT for in vitro embryo production in this species. Yet, further investigation of developmental competence and the factors influencing blastocyst quality and viability is required.